Lipase Inhibition and Antiobesity Effect of Atractylodes lancea - Jiao, Ping; Tseng-Crank, Julie; Corneliusen, Brandon; Yimam, Mesfin; Hodges, Mandee; Hong, Mei; Maurseth, Catherine; Oh, Misun; Kim, Hyunjin; Chu, Min; Jia, Qi (Planta Medica, 2014)
The ethanol extract of Atractylodes lancea rhizome displayed significant lipase inhibition with an IC50 value of 9.06 µg/mL in a human pancreatic lipase assay from high-throughput screening. Bioassay-guided isolation led to the identification of one new polyacetylene, syn-(5E,11E)-3-acetoxy-4-O-(3-methylbutanoyl)-1,5,11-tridecatriene-7,9-diyne-3,4-diol (7), along with six known compounds (1–6). The structure of compound 7 was determined based on the analysis of NMR and MS data. Among these seven lipase inhibitors, the major compound atractylodin (1) showed the highest lipase inhibitory activity (IC50 = 39.12 µM). The antiobesity effect of the ethanol extract of Atractylodes lancea rhizome was evaluated in a high-fat diet-induced obesity mice model at daily dosages of 250 mg/kg and 500 mg/kg body weight for 4 weeks, and treatment with this extract demonstrated a moderate efficacy at the 500 mg/kg dose level.
Keywords: Atractylodes lancea; Asteraceae; pancreatic lipase; lipase inhibitor; atractylodin; polyacetylenes; DIO mice